2013
DOI: 10.3791/50568
|View full text |Cite
|
Sign up to set email alerts
|

Cell Death Associated with Abnormal Mitosis Observed by Confocal Imaging in Live Cancer Cells

Abstract: Phenanthrene derivatives acting as potent PARP1 inhibitors prevented the bi-focal clustering of supernumerary centrosomes in multicentrosomal human cancer cells in mitosis. The phenanthridine PJ-34 was the most potent molecule. Declustering of extra-centrosomes causes mitotic failure and cell death in multi-centrosomal cells. Most solid human cancers have high occurrence of extra-centrosomes. The activity of PJ-34 was documented in real-time by confocal imaging of live human breast cancer MDA-MB-231 cells tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(34 citation statements)
references
References 16 publications
3
31
0
Order By: Relevance
“…As a first approach to analyze the potential of PARP inhibition (PARPi) as monotherapy against GBM we evaluated self-renewal capability, which is a marker of stemness in GSCs, using neurospheres formation assay in primary patient-derived PTEN-proficient GSCs TG1 [ 21 ] with two different PARP inhibitors: PJ34 (IC 20 nM) and olaparib (IC 5 nM). PJ34 targets mainly PARPs synthesizing proteins but some off-target effects have also been reported, suggesting the effect of PJ34 on cancer cells may not be attributed exclusively to PARP inhibition [ 22 , 23 ]. For that reason we also used the clinically relevant PARPi olaparib.…”
Section: Resultsmentioning
confidence: 99%
“…As a first approach to analyze the potential of PARP inhibition (PARPi) as monotherapy against GBM we evaluated self-renewal capability, which is a marker of stemness in GSCs, using neurospheres formation assay in primary patient-derived PTEN-proficient GSCs TG1 [ 21 ] with two different PARP inhibitors: PJ34 (IC 20 nM) and olaparib (IC 5 nM). PJ34 targets mainly PARPs synthesizing proteins but some off-target effects have also been reported, suggesting the effect of PJ34 on cancer cells may not be attributed exclusively to PARP inhibition [ 22 , 23 ]. For that reason we also used the clinically relevant PARPi olaparib.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that apart from PARP inhibition, some of these molecules target a variety of kinases implicated in signal transduction pathways in both healthy and malignant cells [27]. Unexpectedly, this research also disclosed that a group of phenanthrene derivatives acting as PARP inhibitors, exclusively kill human cancer cells without affecting benign cells [28][29][30][31][32]. Unlike other PARP inhibitors, these small molecules exclusively eradicated a variety of human cancer cells without affecting proliferating and non-proliferating healthy somatic cells.…”
Section: Introductionmentioning
confidence: 90%
“…After years of research based on PJ34-induced PARP inhibition in a variety of cell types under pathological conditions [1,2,8], additional activities of PJ34 have been disclosed. It was observed that PJ34 causes an irreversible cell growth arrest in cancer cells, that it interferes with angiogenesis, and, most interestingly, that PJ34 exclusively eradicates human cancer cells [29,30,39,40].…”
Section: Pj34 Efficiently Eradicates a Variety Of Human Cancer Cells mentioning
confidence: 99%
See 2 more Smart Citations